2012
DOI: 10.1016/j.jvs.2012.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after accessory renal artery coverage during endovascular aortic aneurysm repair

Abstract: This study is the largest to date with the longest follow-up relating to ARA coverage. Contrary to previous reports, renal infarction after ARA coverage is common. Nevertheless, coverage is well tolerated based upon preservation of renal function without additional morbidity. These results support the long-term safety of ARA coverage for EVAR when necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 14 publications
5
56
0
1
Order By: Relevance
“…Prior reports indicate that intentional coverage of ARAs during EVAR appears to be safe. [8][9][10][11][12] However, some of these studies have important limitations, including lack of analysis of clinical, laboratory, and anatomical data using standardized definitions, such as renal function deterioration measured using changes in estimated glomerular filtration rate (eGFR) and chronic kidney disease (CKD) stage. In addition, prior reports have not included a control group comprised of patients who had preservation of the entire kidney parenchyma during EVAR.…”
mentioning
confidence: 99%
“…Prior reports indicate that intentional coverage of ARAs during EVAR appears to be safe. [8][9][10][11][12] However, some of these studies have important limitations, including lack of analysis of clinical, laboratory, and anatomical data using standardized definitions, such as renal function deterioration measured using changes in estimated glomerular filtration rate (eGFR) and chronic kidney disease (CKD) stage. In addition, prior reports have not included a control group comprised of patients who had preservation of the entire kidney parenchyma during EVAR.…”
mentioning
confidence: 99%
“…Previous studies documented that the coverage of ARAs by endografts can be well tolerated in the short-and medium-term without significant impairment of renal function or deterioration of hypertension. [5][6][7][8][9][10][11] In contrast, Greenberg et al 10 reported that postoperative renal infarction was detected in 84% of patients after EVAR with ARA coverage, and that the mean volume of the infarcted area was 12% of the total renal volume, indicating a certain degree of ischemic damage to the kidney parenchyma. Malgor et al 11 reported that coverage of ARAs larger than 3 mm in diameter during EVAR could result in type II endoleak leading to aneurysm enlargement.…”
Section: Discussionmentioning
confidence: 98%
“…Greenberg et al evaluated postoperative eGFR values in EVAR-treated patients with an accessory renal artery, and compared patients in whom the accessory renal artery was occluded and patients in whom the accessory renal artery was preserved, with no significant difference observed between the two groups. 14) Occlusion of the accessory renal artery may, therefore, have no clinical significance.…”
Section: Discussionmentioning
confidence: 99%